1981
DOI: 10.1037/0022-3514.41.4.725
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs in paranormal phenomena and locus of control: A field study.

Abstract: Beliefs in paranormal phenomena and their relationship to locus of control were investigated for four groups that varied in terms of their involvement with paranormal practices. Subjects completed a questionnaire designed to assess degree of involvement and beliefs in paranormal phenomena, locus of control, sociopolitical attitudes, and demographic characteristics. It was predicted and found that (a) paranormal beliefs increased as involvement increased; (b) internality increased as involvement increased; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 23 publications
(24 reference statements)
2
25
0
Order By: Relevance
“…1 Although belief in psychic phenomena may be irrational in a scientific sense, involvement in psychic practice may be quite rational in the sense that it provides social and economic benefits as well as status and professional standing. A similar argument was advanced by McGarry and Newberry (1981) to explain why internal locus of control should be higher in practitioners than in lay believers. It is not suggested that the practitioners were engaged in their practice primarily for financial reasons; rather that the various benefits of professional practice could provide an additional motivation to sustain high levels of belief.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…1 Although belief in psychic phenomena may be irrational in a scientific sense, involvement in psychic practice may be quite rational in the sense that it provides social and economic benefits as well as status and professional standing. A similar argument was advanced by McGarry and Newberry (1981) to explain why internal locus of control should be higher in practitioners than in lay believers. It is not suggested that the practitioners were engaged in their practice primarily for financial reasons; rather that the various benefits of professional practice could provide an additional motivation to sustain high levels of belief.…”
Section: Discussionmentioning
confidence: 85%
“…The proposition that a preference for rational thinking might be related to commitment to psychic practice seems somewhat analogous to the observation by McGarry and Newberry (1981) that locus of control was more internal in the group of psychic readers than other groups (subscribers to a newsletter, visitors to a psychic fair, and students with no particular interest; effect sizes were not given). Further, belief in the paranormal was correlated with internal locus of control in individuals with high involvement in psychic practice (correlation coefficient of .39 in the group of psychic readers), but tended to be associated with an external locus of control in individuals with low involvement (.13, ns, in the group of students).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Many other researches have found that people who believe in paranormal phenomena especially among college and university students do not generally reject the notion of mainstream science or technology (Schouten, 1983). Also, some research concludes that in some cases people who have higher education and intellectual abilities tend to believe in paranormal phenomena (McGarry and Newberry, 1981).The further studies shown there are significant gender gaps among the paranormal believers. Here the women believe in paranormal phenomena more their male counterparts.…”
mentioning
confidence: 99%